(3fUjMI GdVGd aj GdEeGeIs - (3eMeO QVG Hf bGSe Hf eMeO GdZQGhj, J (B1385(3g` (B1965(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj QaY GdSeGA HdG YeO (B... (3hWabJ CMQQ aj gPg GdChQGb eSJYjfG HGdcQje GdQRGb eG QSehg aj OaGJQge heG RHQhg aj RHQge ef GdaVGFd Edi jYShH GdEjeGfs
(3BNQgG (B:s
(3BNQgG(B: (3hdjJ TYQj eY Gfge jMQQhf gPg GdaVGFd hGdefGbH dg Ydjg GdSdGe aj cJHge jbhdhf HJaVjd ZjQg Ydjg hjMcehf HJbOjeg Mce Gddg HjffG hHjfge HGdMb hgh NjQ GdMGcejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 128s
(3GdPQjYI, L (B24: 111s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds